Burnett spectral method for the spatially homogeneous Boltzmann equation. (30th March 2020) - Cai, Zhenning; Fan, Yuwei; Wang, Yanli
Highlights: Spectral method using Burnett polynomials is developed for Boltzmann equation. Computational cost is O(M 8 ) for general collision kernels. BGK-type modelling techniques are seamlessly integrated into the new method. The data structure to achieve high cache hit ratio is discussed in detail. The numerical scheme to compute all the coefficients accurately is proposed. Abstract: We develop a spectral method for the spatially homogeneous Boltzmann equation using Burnett polynomials in the basis functions. Using the sparsity of the coefficients in the expansion of the collision term, we reduce the computational cost by one order of magnitude for general collision kernels and by two orders of magnitude for Maxwell molecules. The proposed method can couple seamlessly with the BGK-type modelling techniques to make future applications affordable. The implementation of the algorithm is discussed in detail, including a numerical scheme to compute all the coefficients accurately, and the design of the data structure to achieve a high cache hit ratio. Numerical examples are provided to demonstrate the accuracy and efficiency of our method.